EFFECT OF SOME BIOLOGICAL AND CHEMICAL PESTICIDES IN CONTROLLING TUTA ABSOLUTA OF TOMATO - M., Haitham M..; Birwari , M. A; AL-Qadir, S. Abd (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted at the open fields of the Agricultural Research Station in Dohuk Governorate during the year 2019 on the tomato crop, a local variety. In this study, the effect of chemical pesticides (Imidamex, Matrixine plus) and biological pesticides (Antario KAB,  Biocure) were tested on the percentage of leaf infection, number of larvae, the percentage of fruit infestation and the rate of productivity of one plant. The results revealed that the lowest percentage of leaf infection and the lowest number of larvae appeared with plants treated with Biocure, with an average of 22.7% and 0.36 larva/leaf, respectively. Whereas, the lowest infection rate for fruits and the highest productivity of plants appeared of plants treated with Antariocap, as the rates were 2 fruits/plant and 7.32 kg/plant, respectively. The results showed the superiority of the Antariocap pesticide in controlling this insect, as it had the highest reduction rate in the infested tomato fruits, at a rate of 90.4%.